Langerhans Cell Histiocytosis: A Diagnostic Challenge in the Oral Cavity - Mehmet Ali Altay; Alper Sindel; Öznur Özalp; Burak Kocabalkan; İrem Hicran Özbudak; Ramazan Erdem; Ozan Salim; Dale A. Baur (Case Reports in Pathology, 2017)
Background. Langerhans cell histiocytosis (LCH) is a rare disorder of the reticuloendothelial system with unknown etiology. This report aims to present a case of LCH with diffuse involvement of the oral cavity and to raise awareness of the distinguishing features of this diagnostically challenging entity. Case Report. A 26-year-old male patient presented with complaints of teeth mobility, intense pain, and difficulty in chewing. Intraoral and radiological examinations revealed generalized gingival hyperplasia and severe teeth mobility with widespread alveolar bone loss. Periodontal therapy was performed with no significant improvement. An incisional biopsy revealed Langerhans cells and positive reaction to S-100 and CD1, and the patient was diagnosed with LCH. The patient underwent systemic chemotherapy with vinca alkaloids and corticosteroids. Regression of gingival lesions, as well as significant decrease in mobility of the remaining teeth and severity of pain, was achieved during 12 months of follow-up. Conclusion. The rarity and variable system involvement of LCH necessitate a multidisciplinary approach be carried out for accurate diagnosis, effective treatment, and an uneventful follow-up. Awareness of oral manifestations of LCH may aid clinicians greatly in reducing morbidity and mortality associated with this debilitating condition.